The Effectiveness of Problem based Learning Methods to Improve Higher Level Thinking Skills of SMP Negeri 8 Surakarta - Maulina, Sela; Nuryadi, N; Wahyudi, Nanang Sahid (Universitas Muhammadiyah Surakarta, 2023)
High level thinking skills in Indonesia are still low, as seen from the results of a survey conducted by the Organization for Economic Cooperation and Development (OECD) using the Program for International Student Assessment (PISA) test in 2018. Education in Indonesia is ranked 74 out of 76 countries. The purpose of this research is to find out whether the problem based learning method is effective in improving students higher order thinking skills. The method used in this research is a quantitative method. The sampling technique was carried out using a purposive sampling technique in which the researcher chose the cases to be included in the sample based on the characteristics of the assessment , so the sampling technique was carried out with certain considerations. In the research, it was found that the problem based learning method was effective in increasing students higher order thinking skills. So it can be concluded that the problem based learning method can be used to improve students higher order thinking skills.